2022
DOI: 10.1161/svin.121.000298
|View full text |Cite
|
Sign up to set email alerts
|

Association of the RNF213 p.R4810K Variant With the Outer Diameter of Cervical Arteries in Patients With Ischemic Stroke

Abstract: BACKGROUND We investigated the impact of the p.R4810K variant of RNF213 (ring finger protein 213) gene, a susceptibility gene of moyamoya disease in East Asia, on the outer diameter of cervical parts of carotid and vertebral arteries (VAs). METHODS We examined consecutive Japanese patients with ischemic stroke who underwent carotid ultrasonography between 2015 and 2019. Patient background and the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The novel findings in the present study were the high rate of peripheral vascular disease history in carriers and a strong association of the p.R4810K variant with ECAS. A recent study verified that the p.R4810K variant carriers exhibit smaller outer diameters of the cervical arteries compared with non-carriers with ischaemic stroke 29. In addition, some previous cases have demonstrated that the RNF213 p.R4810K variant impacts arteries throughout the body, such as the abdominal aorta, renal artery and pulmonary artery 30–32.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The novel findings in the present study were the high rate of peripheral vascular disease history in carriers and a strong association of the p.R4810K variant with ECAS. A recent study verified that the p.R4810K variant carriers exhibit smaller outer diameters of the cervical arteries compared with non-carriers with ischaemic stroke 29. In addition, some previous cases have demonstrated that the RNF213 p.R4810K variant impacts arteries throughout the body, such as the abdominal aorta, renal artery and pulmonary artery 30–32.…”
Section: Discussionmentioning
confidence: 90%
“…A recent study verified that the p.R4810K variant carriers exhibit smaller outer diameters of the cervical arteries compared with non-carriers with ischaemic stroke. 29 In addition, some previous cases have demonstrated that the RNF213 p.R4810K variant impacts arteries throughout the body, such as the abdominal aorta, renal artery and pulmonary artery. 30–32 The evidence suggests that the variant of RNF213 might play an essential role in the multiple circulatory systems.…”
Section: Discussionmentioning
confidence: 99%
“…APOE gene was genotyped using a fully automated gene analysis system (GTS-7000; Shimadzu Corporation, Kyoto, Japan). GTS-7000 directly detected single-nucleotide polymorphisms (SNPs) in 1μL of whole blood samples using a polymerase chain reaction [ 17 ]. We examined two SNPs, rs429358 and rs7412, that determine the APOE ɛ allele.…”
Section: Methodsmentioning
confidence: 99%